Derrida and Comparative Philosophy - BURIK, Steven (Institutional Knowledge at Singapore Management University, 2014)
This article argues that Derrida’s thinking is relevant to comparative philosophy. To illustrate this, at various stages classical Daoism is compared with Derrida’s thought, to highlight Derrida’s “applicability” and to see how using Derrida can contribute to new interpretations of Daoism. The article first looks into Derrida’s engagement (or lack thereof) with non-Western thought, and then proceeds to his extensive work regarding language and translation, comparing this with views on classical Chinese language and translation of key Daoist characters. It then explores Derrida’s efforts at opening up philosophy to its outside, and argues that he was very much concerned with other ways of thinking and their possible influence on Western thought. The final section argues both that Derrida’s abiding concern with otherness and alterity forms a fertile background from which to reinvestigate traditional interpretations of classical Daoism and that employing his way of thought can lead us to interesting new perspectives on Daoism.